(untitled) (Asian Journal of Medical and Biological Research, 2022)
Preventive measures to combat with Newcastle disease virus (NDV) can be achieved by vaccination programs that are practiced in many countries of the world. Even after vaccination outbreaks of NDV occurred in the flock indicate that vaccination against NDV cannot provide effective immunity that may cause disease in partially vaccinated flock. Hence, the objectives of this study was to development of flock immunity in chicken against Newcastle disease in a local community. In this study a vaccination programme for the native flock in a locality (Dhamrai, Savar, Dhaka, Bangladesh) was conducted and effectiveness of the Ranikhet disease vaccine (RDV) was identified with detection of antibody titers that may protect the native flocks against the disease but mortality or the infection was present. The study showed that after routine vaccination with BCRDV (Baby Chicks Ranikhet Disease Vaccine) and RDV (Ranikhet Disease Vaccine) vaccine the native chicken showed high antibody titre in native chicken. Overall herd immunity of native chickens can be achieved if the maximum (>80%) chicken obtains high antibody titers (log2 haemagglutination inhibition titer ≥3) after vaccinations. So, it can be concluded that successful vaccinations programme is the key point to control NDV with higher herd health immunity. Asian J. Med. Biol. Res. 2022, 8 (1), 37-41